Blockchain and civil proceedings: points of convergence - Davydova, Iryna; Nahnybida, Volodymyr; Adamova, Olena; Zhurylo, Serhii; Tokareva, Vira (DIXI, 2022)
The rapid development of information technology and the creation of an information society requires the transformation of all spheres of public life. Justice and the civil process remain unchanged, as the latest information technologies have become an indispensable tool in the field of justice for the effective governance and proper functioning of democracy, and on the other hand they remain a significant challenge. Given these circumstances, it is important to analyze the features of the introduction of blockchain technology in civil proceedings and to explore points of contact on this issue. The work aims to study the place of blockchain in civil proceedings, analysis of problematic issues, and prospects for the introduction of blockchain technologies in civil cases. The object of research is the points of сonvergence between the blockchain and the civil process. The subject of the study is the social relations that arise, change and end when using blockchain technologies in civil proceedings. The research methodology is a set of philosophical, general scientific, and special methods of scientific knowledge, such as comparative law, hermeneutic, historical, method of analysis, generalization, synthesis, and analogy. As a result of the research, international trends in the use of blockchain technologies in civil proceedings were analyzed, as well as attention was paid to national developments on the research topic. In addition, the article considers the institutions of civil procedural law, in which it is possible and appropriate to use blockchain technology. The use of this technology will significantly change the usual rules of civil proceedings and may change the procedural guarantees of judges.